PERANAN MANAJEMEN STRATEGI DALAM PENYELENGGARAAN PENDIDIKAN DI INDONESIA - Gunawan, Kazan (Jurnal Inovasi Pendidikan, 2010)
Global, regional, as well as local competitions demand all the agents of educational organizations should possess dynamic, critical, creative, and strategic conceptions responding the escalating challenges. On the other side, the process of conducting education in Indonesia nowadays is rightly tending to be static. It hasn't arrived at provisioning academic as well as administrative personnel who are capable of thinking and taking measures strategically or improving the organizations. The matters arising are that all the agents of previous educational organizations, particularly the state educational institution are still so dependent upon government subsidy that they ignore exercising the strategic management. Nevertheless, in its implementation, the strategic management also has limitations, primarily matters related with the agents' interpretation toward organizational environments which are quite varied. This article is addressed toward the discussion of the role of strategic management in conducting education in Indonesia. It is virtually hoped that all educational administrators are able to determine vision and mission, identify mandate and core competition, carefully analyze the tendency of strategic environments so that they can produce an accurate strategy and implement the indicated strategy in a correct manner.